Comparison of data forwarding mechanisms for AMI networks (2012)
Advance Metering Infrastructure (AMI) networks are often deployed under challenging and unreliable conditions. One of the issues for the transmission of data packet in these unreliable networks is the routing of packets, because routing paths may behave differently from the time when the route is discovered to the time when a data packet is forwarded. In addition, control packets may get lost and give routers an inconsistent view of the network. © 2012 IEEE.